ANALOG PID CONTROLLER IMPLEMENTATION WITH ANTI-WINDUP SCHEME - ADI NUGROHO (NIM 13202118), LISTYANTO
Every actuator is subject to saturation because of its limitation. Actuator saturation is a condition that creates a difference between plant input and control output. This phenomenon, which is called windup effect, causes system's performance degradation. Therefore, a controller with anti-windup implementation may be required to remedy the problem. It will reduce the poor performance due to windup effect in the form of overshoot damper, stabilization, and settling time improvement. A controller with anti-windup technique is then designed and implemented using analog circuit such as LM 348N op-amp and OP07. Astrm anti-windup method is chosen to be implemented here among many anti-windup technique alternatives. The controller is built as a module and PID tuning methods are not studied here. Potentiometers are used in the implementation of controller parameters setting, i.e Kp, Ti , Td , Tt parameters, and saturation limit. For the effectiveness and efficiency of the controller usage, switches are used to easily change the system's configuration: with or without saturation, and saturation without or anti-windup. The controller module has also been tested on Control Systems Laboratorys DC Motor. The test results show that the controller module works well and it can be used for analog control system laboratory experiments.